Boosting Sustainable Agriculture by Arbuscular Mycorrhiza under Stress Condition: Mechanism and Future Prospective. (29th December 2022) - Chauhan, Surya; Mahawar, Sonam; Jain, Devendra; Udpadhay, Sudhir K.; Mohanty, Santosh Ranjan; Singh, Abhijeet; Maharjan, Elina
Abstract : Global agriculture is frequently subjected to stresses from increased salt content, drought, heavy metals, and other factors, which limit plant growth and production, deteriorate soil health, and constitute a severe danger to global food security. Development of environmentally acceptable mitigation techniques against stresses and restrictions on the use of chemical fertilizers in agricultural fields is essential. Therefore, eco-friendly practises must be kept to prevent the detrimental impacts of stress on agricultural regions. The advanced metabolic machinery needed to handle this issue is not now existent in plants to deal against the stresses. Research has shown that the key role and mechanisms of arbuscular mycorrhiza fungi (AMF) to enhance plant nutrient uptake, immobilisation and translocation of heavy metals, and plant growth-promoting attributes may be suitable agents for plant growth under diversed stressed condition. The successful symbiosis and the functional relationship between the plant and AMF may build the protective regulatory mechansm against the key challenge in particular stress. AMF's compatibility with hyperaccumulator plants has also been supported by studies on gene regulation and theoretical arguments. In order to address this account, the present review included reducing the impacts of biotic and abiotic stress through AMF, the mechanisms of AMF to improve the host plant's capacity to endure stress, and the strategies employed by AM fungus to support plant survival in stressful conditions.